A study of the influence of high-energy electron irradiation on the deformation of the plexiglas during the bending test - Kupchishin, A.I.; Niyazov, M.N.; Taipova, B.G.; Khodarina, N.N.; Shakhanov, K.Sh. (Recent Contributions to Physics, 2018)
Experiments was carried out on the dependence of deformation (ε) voltage (σ) when the bending test of non-irradiated and irradiated (electrons) of the samples patterned plexiglass and the PCB. It is established that irradiation leads to a noticeable change in the deformation and strength characteristics of the material, manifested in a decrease in plasticity. Relative deflection striped acrylic plastic after irradiation is changed to 20%, and the pyramid – 40%. In this case, the strength change does not occur. Visual analysis shows that the light transmittance (transparency) is reduced, the samples are colored in brown. Accounting for the horizontal component does not significantly affect the value of the relative elongation. Were obtained based on stress-strain for samples of the PCB, wherein the bending occurs. The maximum load (tensile strength) and the maximum deflection boom preceding the moment of failure are calculated. For samples of brown textolite, the strength limit is 67 MPa, and for yellow – 102 MPa, and εmax= 100 and 95%.The obtained curves are satisfactorily described in the framework of linear (for samples of striped and corrugated Plexiglas) and exponential models (for textolite). As ε increases, ε increases according to a linear and exponential law.